Differences in Knowledge Science in Islamic Education Philosophy Perspective - Sukman Sappe (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
The dichotomy of science is the separation between general science and religion, which then develops into other dichotomic phenomena. The term science dichotomy in various historical literature, including the afterlife and world sciences, syar'iyah science and ghairu syar'iyyah Science, al-'ulum al-diniyyah and al-'ulum al-'aqliyyah, Islamic Knowledge and Non-Islamic Knowledge ( English), Hellenic and Semitic (Greek). The consequences of the dichotomy, as mentioned as the terms of the dichotomy, have implications for the alienation of the religious sciences to modernity and keep the progress of science away from spiritual values. In the perspective of Islamic education, science is an in-depth knowledge of the results of earnest efforts (ijtihād) from Muslim scientists ('ulamā' / mujtahīd) on practical and ukhrāwī issues by originating from the revelations of Allah Almighty so that science grows and develops hand in hand with religion. In the history of Islamic civilization, scholars live in harmony with scientists, many scientists found in Islam, as well as scholars.